337 Metabolic Foundations of Microbiota-Host Interactions. (30th November 2020) - Dodd, Dylan
Abstract: The gastrointestinal tract of mammals is home to a dense population of microbes which influence host physiology and health. One of the most concrete ways that the gut microbiota impacts host biology is through the production of hundreds of chemically diverse small molecules. These molecules are absorbed into the bloodstream, where they reach concentrations similar to those achieved by pharmaceuticals and bind host receptors leading to changes in cellular and organ physiology. Here I will summarize recent work from our group and others that show how microbially sourced metabolites alter health and physiology of the host. I will also discuss how mechanistic studies of small molecules from the microbiota are enabling new therapeutic approaches to harness the metabolic potential of the gut microbiota.